Eficácia do amicarbazone aplicado isoladamente ou em mistura no controle de plantas daninhas - Oliveira, Eli Carlos de (2010)
New herbicides are launched in order to improve the control of weed species. The herbicide amicarbazone is a product of recent introduction in the growing of corn, and therefore it is necessary to evaluate its effectiveness in controlling weeds that infest corn crops. The objective of this study was to evaluate the efficiency of the herbicide amicarbazone, applied alone or in mixtures with other herbicides used in the growing of corn. Six experiments were carried out in greenhouse involving six species of weeds. In the experiments two irrigation intervals were used, while the first interval was irrigated immediately after the sowing and the herbicide application. In the second interval, the vessels containing the species of weed plants were irrigated after 20 days. The weeds which were used in the six experiments were: Ipomoea grandifolia, Euphorbia heterophhylla, Bidens pilosa, Digitaria horizontalis, Brachiaria plantaginea and C. echinatus. The results obtained showed that for D.horizontalis all the mixtures involving amicarbazone in a dose of 0,28 kg ha-1 were effective, unlike the isolated application of the product which did not show any control. For the species Euphorbia heterophylla, the best mixture in the control was observed between amicarbazone and alaclor at doses of 1,44 kg ha-1 and 2,40 kg ha-1. Between amicarbazone and acetochlor the best control was observed at doses of 1,51 kg ha-1. Amicarbazone at a dose of 0,28 kg ha-1 and s-metolachlor at a dose of 1,44 kg ha-1, when applied alone did not control I. Grandifolia in the interval of 20 days of drought until 20 DAA. In the control of Bidens pilosa, the isolated application of amicarbazone at a dose of 0,28 kg ha-1, and in all the tested mixtures were effective in controlling this species. Amicarbazone applied alone at a dose of 0,28 kg ha-1 did not control C. echinatus. The mixture between this herbicide with the other ones controlled this species. The herbicide amicarbazone at a dose of 0,28 kg ha-1applied alone did not control C. echinatus. However, in the mixtures, all combinations between amicarbazone either in tank or formulated mixtures were highly effective in the control of Brachiaria plantaginea.